Introduction to software for chemical engineers - Martin, Mariano Martin (Boca Raton : Taylor & Francis, 2015)
'This book provides a quick reference guide to the use of different software packages for chemical engineering applications so that readers can become familiar with their capabilities. The book covers a range of software packages from Excel and general mathematical packages such as MATLAB or Mathematica, to process simulators, CHEMCAD or ASPEN, equation-based modeling languages, gProms, EMSO, optimization software such as GAMS or specialized software like CFD or DEM codes that are applied to a number of representative examples from the design of chemical reactors, to cooling towers and chemical processes and operation. Each chapter covers a general introduction to the software, the basis behind the scenes as well as a few typical applications and examples.'--
Includes bibliographical references and index.
Keywords: Chemical engineering -- Computer programs